PERBANDINGAN KARAKTERISTIK SKD 11 MOD TERHADAP SKD 11 - Ariobimo, Rianti Dewi Sulamet (Program Studi Teknik Mesin, Universitas Trisakti, 2007)
As mentioned in the previous paper, SKD-11 Mod. is made to upgrade SKD-11properties especially in heat treatment process by modify its chemical composition. This research isconducted to see the improvement that SKD-11 Mod. gain compare to its origin metal, which isSKD-11.